Supra Soft b-Compact and Supra Soft b-Lindle÷F Spaces - Mustafa, Jamal (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
The purpose of this paper is to introduce and study the concepts of supra soft b-compact and supra soft b-Lindelˆf spaces. Also we study several of their properties and characterizations in details. Furthermore, the invariance of these kinds of spaces under some types of supra soft mappings and their hereditary properties are also investigated